INFRA-RED STUDIES OF AMMONIATION OF PILLARED MONTMORILLONITES - Witkowski S.; Sojka Z.; Dyrek K.; Fijal J.; Olkiewicz S.; Fink P.; Hobert H. (My University, 2000)
Ammoniation of montmorillonites pillared with polyhydroxo-complexes of Al was performed in flow conditions at 773-1073 K and monitored by IR spectroscopy. Interaction of the clay with ammonia revealed exchange of terminal and bridging -OH groups by NH2-, NH- and N-species depending on the reaction temperature. Amination begins at 773 K while formation of NH groups starts at 873 K. Transformation of NH- into N-species occurs at 973 K. A mechanism for the ammoniation reaction is proposed and the series of the relative reactivity of OH groups was established: Si-150;OH > Mg-OH-Mg > Al-OH-Mg > Al-OH-Al. This series was rationalized in terms of accessibility of the OH groups.